Optimization of Electrospinning Temperature Control System IoT-Based with DHT21 - Widayani, Della Astri; Hikamiah, Luluk Arifatul; Nugroho, Panji Setyo; Ariyanto, Dewa Pascal; Amaratirta, Jasmine Cupid; Harjunowibowo, Dewanto; Rezeki, Yulianto Agung (Universitas Syiah Kuala, 2024)
Electrospinning is a method of making nanomaterials that has a fairly easy and flexible process that can produce nanofiber continuously. Nanofiber morphology from the electrospinning process is influenced by several parameters, one of them is temperature as an environmental parameter. If there is no temperature control system in the electrospinning system, it will be difficult to maintain the consistency of the morphology nanofiber and at certain temperatures, nanofibers are not formed. Therefore, this study aims to develop a temperature control system for electrospinning called the Electrospinning Temperature Control (ETC) System and connect it with an internet-of- things (IoT) platform to understand the dynamics of the temperature control process, upload temperature data to the cloud, and remote monitoring. The method used by designing and building system hardware and software, calibrating DHT21 as a temperature sensor and testing system performance. The results show that the calibration of the DHT21 sensor has an accuracy rate of 94.95% and a precision rate of 98.93%, while the results of the performance test show that the system can raise, maintain, and lower the temperature. Further performance testing reveals that the ETC system can operate within a temperature range of 2040C. The IoT system using the Blynk App allows users to remote and monitor easily, and using Google Sheets as a cloud database. The ETC system was successfully built and can be applied to electrospinning experiments.